SPECIFIC ASPECTS OF THE INTEGRATION OF THE CENTRAL ASIAN STATES DURING GLOBALIZATION PROCESSES (American Journal of Interdisciplinary Research and Development, 2024)
In the article, the issues that have been implemented and should be implemented in the process of integration of the Central Asian countries in the conditions of the modernizing Uzbekistan have been scientifically analyzed on the basis of periodical press materials.